PENGARUH PROFITABILITAS, LIKUIDITAS DAN NILAI PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - mariyanti, mariyanti; Vargo Christian L. Tobing (SCIENTIA JOURNAL, 2021)
This study aims to examin the effect of profitability, liquidity, and company value on stock prices on LQ45 companies listed on the Indonesia Stock Exchange either partially or simultaneously. The analytical method used in this study is a quantitative method with data analysis methods namely the Assumption Test and analysis multiple linear regression. The variables in this study are profitability measured using ROA, liquidity measured using CR proxies, and Company Value measured using PBV proxies as independent variables. The dependen variable in this study is the stock price. The population of this study consists of 45 go-public companies that are members of the LQ 45 index listed on the Indonesia Stock Exchange in 2015-2019. Sampling using purposive sampling and obtained 27 companies with a sample size of 135. The data used are secondary data, obtained from IDX Batam City Representative in the form of 2015-2019 financial statements published through the website www.idx.co.id and closing price through the website www.yahoofinance.com. Based on this research t test results note that the variable do not Company Value significantly affects the Stock Price while the Profitability and Liquidity variables affect the Stock Price. And for the f test results show that Profitability Liquidity, and Firm Value simultaneously or or partial effect on Stock Prices.